IDENTIFIKASI KUTU PUTIH PADA TANAMAN ROSELLA(Hibiscus sabdariffa) - Martala Sari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Mealybug damage roselle plant, so it can reduce the productivity of the plant. The purpose of this study identification mealybug on roselle plant. Identification is done using existing preserved specimens using a Zeiss stereo microscope SV11 connected with the camera lucida. The observation of preserved existing infestation is obtained that has the following characteristics: 1) Body oval, convex and white color because his body is covered by a layer of wax, 2) antenna consists of 9 sections, 3) had a great circle of the majority has a great body 4-5 mm, 4) have a multilocular hole of segment VI or VII to VIII, 5) Legs with transparent holes on the stale of the femur and the tibia, 6) Anal Ring large. It can be concluded that these features are found in Phenacoccus solenopsis roselle plant. Keywords: mealybug, roselle, identification